2022
DOI: 10.1111/cfs.12927
|View full text |Cite
|
Sign up to set email alerts
|

Periods of uncertainty: The experience of at‐risk young adult Arabs during the transition to adulthood in the wake of COVID‐19

Abstract: The ongoing COVID‐19 global health crisis has both short‐ and long‐term implications for the lives of young adults worldwide, especially young adults from vulnerable communities. The current exploratory study is the first, to our knowledge, that investigates the impact of the pandemic on the lives of at‐risk young adult Arabs, who are part of a national minority group in Israel. Twenty‐eight at‐risk young adults aged 18 to 25 participated in semistructured interviews regarding the experiences, challenges and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Against the backdrop of the COVID-19 pandemic, the conditions brought about by the crisis likely intensifed preexisting family tensions and contributed to diminished mental well-being, as earlier studies have already indicated [5,22]. Consequently, it is plausible that the pandemic's repercussions might persist beyond its resolution, exerting a lasting impact.…”
Section: Teoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the backdrop of the COVID-19 pandemic, the conditions brought about by the crisis likely intensifed preexisting family tensions and contributed to diminished mental well-being, as earlier studies have already indicated [5,22]. Consequently, it is plausible that the pandemic's repercussions might persist beyond its resolution, exerting a lasting impact.…”
Section: Teoretical Frameworkmentioning
confidence: 99%
“…In terms of COVID-19 and at-risk young adults, there is a good reason to be concerned, as the majority of these vulnerable young people were already struggling, pre-COVID, with the risks and developmental harms associated with many previous stressors including poverty, neglect, food insecurity, housing instability, lower social support, and mental health problems. Te pandemic contributed to greater isolation, family stress, and lower socioeconomic status [21,22]. Recent studies have highlighted at-risk young adults' need for extraordinary support from the state, communities, and nonproft agencies to meet the acute challenges of a pandemic in the context of chronic adversity and deprivation [10,11].…”
Section: Risk and Resilience During Times Of Crisis And Disastermentioning
confidence: 99%